2020
DOI: 10.1007/s12640-020-00191-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Single Head Exposure to GSM-1800 MHz Signals on the Transcriptome Profile in the Rat Cerebral Cortex: Enhanced Gene Responses Under Proinflammatory Conditions

Abstract: Mobile communications are propagated by electromagnetic fields (EMFs), and since the 1990s, they operate with pulsemodulated signals such as the GSM-1800 MHz. The biological effects of GSM-EMF in humans affected by neuropathological processes remain seldom investigated. In this study, a 2-h head-only exposure to GSM-1800 MHz was applied to (i) rats undergoing an acute neuroinflammation triggered by a lipopolysaccharide (LPS) treatment, (ii) age-matched healthy rats, or (iii) transgenic hSOD1 G93A rats that mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…A large number of studies have attempted to better understand the effects of a variety of electromagnetic field intensities over variable periods of time on animals [ 134 , 135 , 136 , 137 , 138 , 139 , 140 ], animal tissues [ 141 ], and cells [ 142 , 143 ]. The recent review by Lee et al [ 140 ] provides an excellent summary of much of the animal literature in this regard.…”
Section: Additional Risks Of Space Flight Into Deep Space and Living ...mentioning
confidence: 99%
“…A large number of studies have attempted to better understand the effects of a variety of electromagnetic field intensities over variable periods of time on animals [ 134 , 135 , 136 , 137 , 138 , 139 , 140 ], animal tissues [ 141 ], and cells [ 142 , 143 ]. The recent review by Lee et al [ 140 ] provides an excellent summary of much of the animal literature in this regard.…”
Section: Additional Risks Of Space Flight Into Deep Space and Living ...mentioning
confidence: 99%
“…Gene expression was altered in neuronal and glial cells of rats pre-treated with lipopolysaccharide, a neuroinflammatory agent, and then exposed to 1800 MHz GSM modulated radiation (SAR = 3.22 W/kg) for 2 hr. [ 101 ]. In rats pre-treated with picrotoxin, a chemical that induces seizures, exposure to pulse-modulated 900 MHz GSM-modulated RF radiation of mobile phones increased regional changes in brain activity and c-Fos expression [ 102 , 103 ].…”
Section: Assumptions Underlying Exposure Limits For Rf Radiation and ...mentioning
confidence: 99%
“…Investigating the effects of a single head exposure to GSM-1800 MHz EMF in LPS-treated rats, we found that GSM signals trigger cell responses in the cerebral cortex affecting expression of genes, phosphorylation of glutamate receptors, neuronal evoked discharges and microglial cell morphology in the cerebral cortex. These effects were not detected in healthy rats submitted to a same GSM exposure indicating that the LPS-triggered neuroinflammatory state sensitize CNS cell responses to GSM signals (Lameth et al 2020;Lameth et al 2017;Occelli et al 2018;Watilliaux et al 2011). The capacity of RF exposure to impact on biological processes strongly depend on the specific absorption rate (SAR) expressed in W/kg, that measures the energy absorbed in the biological tissues.…”
Section: Introductionmentioning
confidence: 99%